Thoracic EndoVascular Stent Graft Repair for Aortic Aneurysm - Kim, Joung Taek (Korean Society for Thoracic and Cardiovascular Surgery, 2011)
BACKGROUND: The number of cases employing thoracic endovascular aortic repair (TEVAR) has been increasing due to lower morbidity and mortality compared to open repair technique. The aim of this study is to evaluate the outcome of TEVAR for thoracic aortic diseases. MATERIALS AND METHODS: Sixteen patients underwent TEVAR from October 2003 to April 2010. Mean age at operation was 59 years (20~78 years), and 11 were male. Indications for TEVAR were large aortic diameter (>5.5 cm) upon presentation in 6 patients, increasing aortic diameter during the follow-up period in 4, traumatic aortic rupture in 3, persistent chest pain in 2, and ruptured aortic aneurysm in one. The mean diameter, length and the number of the stents were 33 mm (26~40 mm), 12 cm (9.5~16.0 cm), and 1.25 (1~2), respectively. Aortography employing Multi-detector computerized tomography (MDCT) technique was performed at one week, and patients were followed up in the out-patient department at one month, 6 months, and one year postoperatively. RESULTS: Primary technical success showing complete exclusion of the aneurysm was achieved in 15 patients. One patient showed a small endo-leak (type 1). Four patients developed perioperative stroke: Three recovered without sequelae, and one showed mild right-side weakness. There was no operative mortality. Diameter of the thoracic aorta covered by stent graft changed within 10% range in 12 patients, decreased by more than 10% in 3, and increased by more than 10% in one during mean follow-up duration of 18 months (1~73 months). There was no recurrence-related death during this period. CONCLUSION: Intermediate-term outcome after TEVAR was encouraging. Indications for TEVAR could be extended for other thoracic aortic diseases.